2023
DOI: 10.9758/cpn.2023.21.2.222
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Adverse Reactions to SARS-CoV-2 Vaccines

Abstract: SARS-CoV-2 vaccines are not free of side effects and most commonly affect the central or peripheral nervous system (CNS, PNS). This narrative review aims to summarise recent advances in the nature, frequency, management, and outcome of neurological side effects from SARS-CoV-2 vaccines. CNS disorders triggered by SARS-CoV-2 vaccines include headache, cerebro-vascular disorders (venous sinus thrombosis [VST], ischemic stroke, intracerebral hemorrhage, subarachnoid bleeding, reversible, cerebral vasoconstriction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 134 publications
0
9
0
Order By: Relevance
“…One group that focused on PASC in the context of the elderly showed that an approximated 30% of patients over the age of 65 developed it (190), while another study showed that Long COVID symptoms were more severe in elderly patients (191), supporting data gathered by the US Census Bureau, though it should be noted that the elderly do not have the highest reported incidence rate of post-COVID symptoms following infection (192). Within the context of vaccination alone, the development of Long COVID has not been extensively addressed, though neuropathic symptoms have been reported, albeit at a lesser occurrence rate than primary infection without vaccination (193)(194)(195). While evidence suggests that those vaccinated before infection have protection against Long COVID (196), symptom development after vaccination alone is a phenomenon that is not understood and warrants preclinical investigation, particularly in the context of the elderly.…”
Section: Revisiting the Network Hypothesis: Immunoregulatory Effects ...mentioning
confidence: 63%
“…One group that focused on PASC in the context of the elderly showed that an approximated 30% of patients over the age of 65 developed it (190), while another study showed that Long COVID symptoms were more severe in elderly patients (191), supporting data gathered by the US Census Bureau, though it should be noted that the elderly do not have the highest reported incidence rate of post-COVID symptoms following infection (192). Within the context of vaccination alone, the development of Long COVID has not been extensively addressed, though neuropathic symptoms have been reported, albeit at a lesser occurrence rate than primary infection without vaccination (193)(194)(195). While evidence suggests that those vaccinated before infection have protection against Long COVID (196), symptom development after vaccination alone is a phenomenon that is not understood and warrants preclinical investigation, particularly in the context of the elderly.…”
Section: Revisiting the Network Hypothesis: Immunoregulatory Effects ...mentioning
confidence: 63%
“…Fatal reactions including thrombotic thrombocytopenia, myocarditis/pericarditis, rhabdomyolysis, and anaphylaxis were noted in a previous review article [12]. Both central and peripheral nervous systems have also been reported to be involved in adverse reactions to mRNA vaccines [13]. Possible central nervous system disorders include venous sinus thrombosis, ischemic stroke, intracerebral hemorrhage, subarachnoid bleeding, reversible cerebral vasoconstriction syndrome, vasculitis, pituitary apoplexy, Susac syndrome, encephalitis, meningitis, demyelinating disorders, transverse myelitis, and epilepsy [13].…”
Section: Introductionmentioning
confidence: 95%
“…The side effects of COVID-19 vaccines include local injection site reactions, fever, fatigue, and various neurological conditions (such as headache, venous sinus thrombosis, encephalitis, epilepsy, Guillain-Barre syndrome, facial palsy, myositis, and dermatomyositis). [ [8] , [9] , [10] , [11] ]…”
Section: Introductionmentioning
confidence: 99%